This is Autism: Breakthrough Research Discoveries - Rowland, David (This is Autism: Breakthrough Research Discoveries, 2021)
This book is a reprinting of nine of the author’s articles about autism that have been previously published in peer reviewed medical journals. The author details herein his discovery of the neurophysiological cause of autism, his development of a litmus test whereby you can know if someone suspected of being autistic has been correctly diagnosed, and his discovery of a rare form of trauma induced autism.